Chlamydia pneumoniae Antibodies and C-Reactive Protein Levels in Patients with Abdominal Aortic Aneurysms - M. A. Sharif; D. A. McDowell; S. A. Badger (The Scientific World Journal)
Introduction. The study aim was to assess the relationship between the presence of antibodies to Chlamydia pneumoniae and abdominal aortic aneurysm (AAA) incidence. Patients and Methods. Consecutive AAA patients and AAA-free controls were recruited prospectively. Serum samples from both groups were examined to determine Immunoglobulin (Ig) A and IgG titres against Chlamydia pneumoniae by ELISA and C-reactive protein (CRP) concentrations. Results were expressed as mean (SD) or median (IQR) and compared using χ2 and Mann-Whitney U tests. A P value of <0.05 was considered statistically significant. Results. Each study group (AAA/nAAA) comprised 250 patients. 196 (78.7%) AAA patients had positive IgA antichlamydial antibody titres, compared to 181 (72.4%) in the control group (P=0.008, OR 2.0, 95% CI 1.2–3.5). However, positive IgG antibody titres were similar (191 versus 203; P=0.222, OR 0.7, 95% CI 0.4–1.3). Average CRP concentrations were higher in AAA individuals. IgA or IgG antibody titres were not related to CRP concentrations. Conclusions. These results demonstrated that the frequent incidence of Chlamydia pneumoniae antibodies within the general population makes it difficult to relate its presence to AAA development, despite the high IgA antibody titres. In addition, raised CRP concentrations in AAA patients are not related to the presence of antichlamydial antibodies.